The Effect of Transformational Leadership on Organizational Citizenship Behavior: The mediating performance of Organizational Commitment - S., A. Pratminingsih; N. , Hayati; M., A. Drajat; P. , Sukandi (International Journal of Psychosocial Rehabilitation, 2020)
Every organization wants to have employees who are willing to work beyond what is stated in the job description because this can increase company productivity. This research will explore the impact of transformational leadership and commitment factors on employee desires in working beyond his job description (OCB). This research utilized explanatory approach with a total sample of 115 respondents. Data of this study is analysis using regression analysis. The results showed that informational leadership and commitment affect organizational citizenship behavior.